Thin-film design : modulated thickness and other stopband design methods - Perilloux, Bruce E. (Tutorial texts in optical engineering ;, 2002)
This text presents several new thin-film design methods that can produce multiple stopbands as well as passbands. It is written for thin-film designers and students with advanced knowledge of multilayer, optical thin-film coatings. The text focuses on coatings that have high reflectance performance requirements in more than one spectral wavelength band or region.